STUDENT MANAGEMENT MODEL - Amini, Amini; Syamsuyurnita, Syamsuyurnita; Hasnidar, Hasnidar (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This research applied product research entitled Student Savings Empowerment Management Model aims to help overcome financial management problems especially at private schools / madrasah related to financial governance. This is associated with low and often inaccurate student tuition fees and government policies that roll out the BOS (school operational assistance) budget budget not every month, and even usually withdrawn by the government for 3 to 6 months. Even so, the obligation to pay teachers salaries must be paid at the beginning of the month for each month on a regular basis. Therefore, it is required a strategic effort of money management from the BOS Fund to be utilized in other financing such as teacher salary, but not violate the rules and regulations that apply. The methodology of this research is descriptive qualitative, with the technique of interview data analysis, document study. Trial model implemented in MIS Mutiara located at Jati Street No. 125 Sei. Send Deli Serdang Regency. After the pilot, the student saving empowerment model can overcome the problem of paying the teacher not on time to be on time, on every 2nd of the month, and able to overcome the monthly operational costs of the school. This research therefore recommends that the model be applied to other madrasah / private schools with the same problems.